Hukum ekonomi Islam : dinamika dan perkembangan di Indonesia - Umam, Khotibul, 1982- (Yogyakarta : Instan Lib, 2009)
On economic law from Islamic perspective.
Includes bibliographical references (p. 127-132).
Keywords: Islamic law -- Economic aspects -- Indonesia; Indonesia -- Economic policy